Geometrizacija prostora in filozofija narave - Vrečko, Janez (Jezik in slovstvo, 2014)
Kosovel's square shape is based on the constructivist abolishment of Euclidian space and Renaissance perspective. Kosovel chose constructivism because it enabled him to synthesise a mechanical technique and organic nature. Kosovel's phrase "hay roofs" serves to represent a polemical treatment of the so-called social order ("socialno naročilo") and illiterate crowds, and in doing so raises the question of tendentious art and social realism.
Keywords: Kosovel, Srečko, 1904-1926; slovenska poezija; constructivism; konstruktivizem; literarna avantgarda; tendenčna umetnost